Experimental and Numerical Study of the Effect of Varying Sinusoidal Bumps Height at the Leading Edge of the NASA LS (1)-0413 Airfoil at Low Reynolds Number - Kunya, Bashir Isyaku; O. Folayan, Clement; Yakubu Pam, Gyang; Anafi, Fatai Olukayode; Muhammad, Nura Muaz (CFD Letters, 2021)
This research work is about numerical simulation and experimental study of the effect of varying sinusoidal bumps (or tubercles) height at the leading edge of the airfoil on efficiency using NASA LS (1)-0413 cross-section profiles. Spalart Allmaras turbulence model was used for numerical solutions. The parameters investigated include, lift, and drag, the angle of attack and bumps height at very low Reynolds number of 4.9 x 104. The results show that bumps on the blade leading edge have an advantage at post-stall angles of attack on the performance and varies with bumps height.